Integrating Silih Asah, Silih Asih, and Silih Asuh in Primary School Character Education - Ansori, Yoyo Zakaria; Agustin, Mubiar; Jatisunda, Mohamad Gilar; Azman, Mohamed Nor Azhari (Universitas Muhammadiyah Surakarta, 2025)
Character education is a foundational pillar in students' moral and social development, particularly at the primary education level. This study examined the role of Sundanese local wisdoms silih asah (mutual enlightenment), silih asih (mutual affection), and silih asuh (mutual care) in shaping students' character across the cognitive, affective, and behavioural dimensions. A qualitative case study design was employed to enable an in-depth exploration of how these values are integrated into the learning ecosystem of a public primary school in Nunuk Baru Village. Data were collected through classroom observations, in-depth interviews, and document analysis conducted within the school setting. Qualitative data were systematically analyzed using NVivo software to support coding, thematic analysis, and data triangulation. The findings indicate that teacher empathy accounted for 30% of compassion-based interactions, peer support behaviours emerged in 25% of observed incidents, and practices reflecting silih asuh, such as a buddy system, were documented 21 times. In addition, spontaneous acts of care and active participation in extracurricular communal activities reflected the authentic internalization of these values. This study highlights the importance of embedding local wisdom into formal schooling as a sustainable approach to fostering prosocial behaviour and strengthening students' moral resilience amid the challenges of globalization.